Anatomical evaluation of first dorsal compartment of the hand – a study in South Indian cadavers. - Suhani, S; Mamatha, H; Bhaskarananda, K; Saraswathi,; Melanie, RD; Naveen, K (Department of Surgery, UKM Medical Centre, 2013)
Morphology of the first dorsal compartment of the hand is often linked with several surgical or orthopaedic complications. It is frequently associated with splitting of the compartment into two sub compartments and more common in patients with de Quervain disease, which supports the claim that this anatomic variation is involved in the pathogenesis of de Quervain disease. Our aim was to evaluate the different anatomic variations of the first dorsal compartment and its possible clinical complications in south Indian cadaveric hands. We studied 94 formalin fixed isolated hands for the morphological study of the 1st dorsal compartment. The length and width of the compartment ranged between 14.07 to 24.17mm and 4.19 to 10.37mm, respectively and the thickness of the extensor retinaculum over the first dorsal compartment was found to vary between 0.11mm to 1.72mm. Septation was seen in 50.74% of the specimens. In majority of cases, extensor pollicis brevis presented with single tendon and in 2.98% cases, it was absent. In contrary to this, multiple tendons of abductor pollicis longus was common observation. Hence, it is handy to have a prior detailed knowledge of existence of the various anatomic variations of first dorsal compartment for the surgeons who treat de Quervian’s tenosynovitis or other related clinical complications, which require steroid treatment as it should be injected to both sub compartments when present.